Factors Affecting The Success of Nanotechnology Product Commercialisation in Malaysia - Mawaddah, Mohamad (2013)
Issues on research, innovation and commercialisation of nanotechnology have since become hot as some began disputing and debating the level of research and innovation on nanotechnology in Malaysia. In Malaysia. although small, nanotechnology based products have begun entering the market. Also, the number of companies commercialising this product is restricted. While studies on the success of nanotechnology commercialisation are being constantly discussed abroad, in Malaysia investigations on the subject are practically small. With this in mind, this study has identified factors closely related to the success of nanotechnology product commercialisation. Among the factors are capital investment, customer focus, management team, business strategy, product quality and company infrastructure. The sample for this study composed 93, consisting of companies currently commerciaIising nanotechnology. Questionnaires and mail were used in the survey process. The hypotheses were tested using correlation and regression analysis. The findings from the correlation reveal that capital investment, customer focus, management team, business strategy, product quality and company infrastructure have significant relationship with the success of nanotechnology commercialisation while regression analysis indicate that the combination of these factors contribute to the success of nanotechnology product commercialisation. However, only capital investment and business strategy showed any real significance on the success of nanotechnology commercialisation. Subsequently, a regression analysis was carried out, to order the importance of these factors. The results revealed that capital investment as being the most important factor, in this study, with coefficient of 0.321 followed by business strategy with P coefficient of 0.3 16. The P coefficients for the other factors (company infrastructure, management team, customer focus and product quality) were small and not that significant.